1983
DOI: 10.1071/bi9830139
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Glycosidase Activities in one Adult and two Suckling Echidnas: Absence of a Neutral Lactase (b-D-Galactosidase).

Abstract: The activities of various glycosidases in homogenates of the small-intestinal mucosa of one adult and two suckling echidnas, Tachyglossus aculeatus, were investigated. The activities of lactase (!i-D-galactosidase), !i-N-acetylglucosaminidase, neuraminidase and ()(-L-fucosidase were higher in the sucklings than in the adult animal. Maltase and isomaltase activities were lower. Sucrase and cellobiase activities were absent or present in trace amounts only. The lactase activity had a pH optimum of 4· 0--4· 5, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…With respect to monotremes, it has been shown that small intestinal neutral lactase activity was entirely absent but, as in marsupials, various acid glycosidases including b-galactosidase, a-L-fucosidase and neuraminidase could be detected in the small intestine of the suckling echidna. These results were consistent with the concept that the oligosaccharides of echidna milk (mainly sialyl and fucosyllactoses) are digested by lysosomal enzymes contained within the enterocytes of the small intestine (Stewart et al, 1983). …”
Section: Urashima Fukuda and Messer Core Units And Lewis X (Galsupporting
confidence: 91%
“…With respect to monotremes, it has been shown that small intestinal neutral lactase activity was entirely absent but, as in marsupials, various acid glycosidases including b-galactosidase, a-L-fucosidase and neuraminidase could be detected in the small intestine of the suckling echidna. These results were consistent with the concept that the oligosaccharides of echidna milk (mainly sialyl and fucosyllactoses) are digested by lysosomal enzymes contained within the enterocytes of the small intestine (Stewart et al, 1983). …”
Section: Urashima Fukuda and Messer Core Units And Lewis X (Galsupporting
confidence: 91%
“…The predominance of lactose in giant anteater milk suggests that the neonate uses lactose as a significant energy source and that the microvilli of the small intestinal mucosa therefore contain an active neutral lactase capable of digesting this disaccharide. It can also be hypothesized that this enzyme was acquired by the ancestral therians prior to the divergence of the marsupials, because, although it has been shown to be absent in monotremes (Stewart et al . 1983) it is present in possums and other non‐macropod marsupials (Messer et al .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the activity of small intestinal lactase is lacking in the suckling neonates of monotremes ( Stewart et al, 1983 ) and Macropodidae marsupials ( Walcott and Messer, 1980 ; Crisp et al, 1987 ; Messer et al, 1989 ), including wallabies and kangaroos. Based on the histochemical observations of the small intestine of the suckling echidna and tammar wallaby, it has been concluded that the milk oligosaccharides are transported by pinocytosis or endocytosis into the small intestinal cells and then enclosed in the supranuclear vacuoles to be moved to the lysosome.…”
Section: Small Intestinal Digestion Of Milk Oligosaccharides In Suckl...mentioning
confidence: 99%